Fiscal Decentralization and Institutional Legacy: Explaining Variations in Human Development Outcomes in Banyumas and Banjarnegara Regencies: Desentralisasi Fiskal dan Warisan Institusional: Menjelaskan Variasi Outcome Pembangunan Manusia di Kabupaten Banyumas dan Banjarnegara - Hibatulloh Akbar Novianto; Rivaldi Mahardika; Athira Zahroh Firdausi Ramadhani (Jurnal Pemerintahan dan Politik, 2026)
Purpose : This study analyzes how fiscal capacity, development priorities, and historical institutional legacies contribute to variations in human development outcomes between Banyumas and Banjarnegara Regencies under decentralization. Design/methodology/approach : This qualitative research uses a descriptive comparative approach with a Most Similar System Design (MSSD). Analysis was conducted in three interrelated stages, integrating BPS documents, RPJMD, official records, and supporting scientific articles. Findings : Variations in development outcomes between Banyumas and Banjarnegara result from the interaction of fiscal capacity, development priorities, and historical institutional legacies. These legacies shape initial regional capacities, influencing how well regions leverage decentralization and leading to differing sustainable HDI outcomes. Practical Implication : Findings suggest fiscal transfer mechanisms should be reviewed and redesigned asymmetrically, accounting for each region’s historical capacity and development needs, to prevent regions from falling further behind under autonomy. An institutional-historical dimension should also be incorporated in analyzing regional development variation. Originality/value : This research integrates fiscal decentralization and historical institutionalism perspectives using MSSD. Unlike prior studies that treat fiscal capacity as a contemporary factor, this study shows it results from historical institutional trajectories shaping development outcomes. Paper type : Research Article